Measuring transboundary water cooperation: learning from the past to inform the sustainable development goals - Saruchera, D.; Lautze, Jonathan F. (International Water Management Institute, 2015)
Water cooperation has received prominent focus in the post-2015 United Nations Sustainable Development Goals (SDGs). While proposals for measuring water cooperation appear to be converging toward a small set of indicators, the degree to which these proposed indicators draw on past work is unclear. This paper mines relevant past work to generate guidance for monitoring the proposed SDG target related to transboundary water cooperation. Potential measures of water cooperation were identified, filtered and applied in three countries (Botswana, South Africa and Zimbabwe). Six indicators were ultimately determined as being suitable for measuring water cooperation. As the SDG process turns its focus to the selection of indicators, the indicators proposed in this paper may merit consideration.